An Investigation of Tardiness Among Freshmen at Universitas Advent Indonesia - Yenni Christina (12th International Scholars Conference 2025, 2026)
This study investigates the prevalent issue of tardiness among freshmen attending Universitas Advent Indonesia (UNAI). The research aimed to identify key factors contributing to students' late arrival in classrooms and to offer practical insights for improving punctuality. A quantitative research design was employed, utilizing a structured questionnaire administered to 44 students aged 17 to 20. Findings indicate that despite a general appreciation for punctuality, a significant portion of students experience tardiness due to poor time management, laziness, and oversleeping. While many students reported feeling stressed when late, a notable minority felt relaxed or indifferent. The majority of students were late 1-2 times per week, and the enforcement of disciplinary measures for tardiness was inconsistent. Nevertheless, most students reported having personal strategies to manage their lateness and acknowledged its disruptive impact on the learning process. Identified strategies for improving punctuality included better planning of morning routines and the use of multiple alarms. The classroom environment was found to have a moderate influence on tardiness. Addressing these multifactorial issues is crucial for enhancing student punctuality and fostering a more conducive learning atmosphere at UNAI.